Development of Virtual Learning for Chemistry Subject based on Constructivism-Contextual Approach - Bakar, Norasiken; Shahbodin, Faaizah; Salam, Sazilah; Ahmad, Ibrahim; Shuhimi, Rozie Ezrina (2010)
This paper highlight the development of virtual learning for chemistry subject. In this research the term virtual learning is used to show the students may see the real materail and simulation that involved in learning process using computer.